Kirk A. Hawkins, Ryan E. Carlin, Leven te Littvay, and Cristóbal Rovira Kaltwasser (Eds.). The Ideational Approach to Populism: Concept, Theory, and Analysis London and New York: Routledge, 2019, pp. xxiv + 437. - Sarsfield, Rodolfo (Revista Latinoamericana de Opinión Pública, 2019)
Resumen